Solving f(x-f(y))=1-x-y

preview_player
Показать описание
If you need to post a picture of your solution or idea:
#ChallengingMathProblems #FunctionalEquations #Functions
via @YouTube @Apple @Desmos @NotabilityApp
@googledocs @canva

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

take y=0 and x=f(0), then f(x-f(y))=f(0)=1-f(0), hence f(0)=1/2. Now again let y=0 and x arbitrary, then f(x-f(y))=f(x-1/2)=1-x. Setting x=t+1/2 we find f(t)=1/2-t.

thatdude_
Автор

Given:
f(x – f(y) = 1 – x – y
To findv
f(x)

Substituting y = 0, x is free:
f(x – f(0)) = 1 – x

Substituting z = x – f(0)
f(z) = 1 – z – f(0)

Substituting z = 0:
f(0) = 1 – f(0)
2f(0) = 1
f(0) = ½

Back-substituting:
f(z) = 1 – z – ½
f(z) = ½ – z.

Resubstituting z = x:
f(x) = ½ – x.


Checking:
f(x – f(y)) = ½ – x + f(y) = ½ – x + ½ – y = 1 – x – y

GirishManjunathMusic
Автор

I like how you explain your methods. Nothing is absolutely perfect but you come pretty close 😊.
Keep doing your work, I’m sure I’m not the only one enjoying the exercises.
(Cheers! From an old school learner)

BlaqRaq
Автор

My method wasn't the simplest one, but it worked. Also, I assumed f is invertible since the composite f(x-f(y)) is linear.
So first, I plugged some values.
x=1 => f(1-f(y)) = -y
x=1 & y=-y => f(1-f(-y)) = y => Therefore 1-f(-x) is the inverse of the function f.
y=1 => f(x-f(1)) = -x
y=1 & x=-x => f(-x-f(1)) = x => Therefore -x-f(1) is also the inverse of the function f.
Therefore -x-f(1) = 1-f(-x)
=> f(-x) = 1 + f(1) + x
=> f(x) = 1 + f(1) - x
So now we plug some more values:
x=0 => f(0) = 1 + f(1)
y=0 => f(x - f(0)) = 1 - x
=> f(x - 1 - f(1)) = 1 - x
x=1 => f(-f(1)) = 0
Now using f(x) = 1 + f(1) - x
x=-f(1) => f(-f(1)) = 1 + f(1) + f(1) = 0
=> f(1) = -1/2
=> f(x) = 1/2 - x

raystinger
Автор

How do we know that this is the only solution ? I mean we have'nt look for other solution so is there any other solution and how do we proof it?

astraff
Автор

I split the difference between your solutions.

Set x = f(y) to get f(0) = 1- f(y) - y.

Set f(0) = -c+1 to get c = f(y) + y

Then substitute back to get c = 1/2

richardfarrer
Автор

Set x = 0
You get: f(-f(y)) = 1 - y
multiply both sides by -1:
-f(-f(y)) = y - 1
define g(x) = -f(x)
so you have: g(g(x)) = x - 1
assuming g(x) is a first-degree polynomial, you can set g(x) = ax + b
then solve for a and b
it's not hard to do
and once you find g(x), it's super easy to find f(x)

armacham
Автор

We have f(x)=-x+1-c
You can put x=0 and then you find c=1/2

rachidtanan
Автор

My solution before watching the video:

Let m = f(0)
Then m = f(f(y)-f(y))
= 1-f(y)-y
Thus f(y) = 1-y-m
So m = f(0) = 1-m, thus m = 1/2
So (changing y to x) we have
f(x) = 1/2 - x

seanfraser
Автор

Very similar to:
f[x+f(y)]=x+y+1
Solved september 6th, 2021,
says the YT algorithm.

elederiruzkin
Автор

Is it correct to set x=y+f(y)? Very convenient.

markosv
Автор

If f(x)= -x + k, then f(y)= -y + m where m and k are constants. Why did you assume that m = k in your explanation in the vedio? Where u said f(y) = - y +k

AliBarisa
Автор

Wow!Slovenia?!!!
SinQ/CosQ a 1x10^6 sir!

SuperYoonHo
Автор

EMEKLERİNİZE SAĞLIK KOLAYLIKLAR DİLİYORUM HOCAM

haliltokmakmatgeo
Автор

how about a proof that there are no other solutions?

VictorStarukhin
Автор

From russia pls
f (0;+inf) : x (0;+inf)
f(x+f(y+xy))= (y+1)f(x+1) -1

ЯрикБибик-що